An accurate model for analysis of composite laminated cylindrical shells under hygrothermal loads - Al-Subari, Saleh Naji Musaed
The present study aims to investigate the combined effect of moisture and temperature on the bending behavior of laminated composite cylindrical shell using an accurate laminate theory. Initially, standard benchmark results based on 3D elasticity solutions are used to assess the range of the applicability of available laminate models. Later, based on the realistic variation of displacements from the elasticity approach, a new 13 term higher order shear deformation theory HSDT13 was proposed for accurate analysis of cylindrical shell strip under hygrothermal and mechanical loading. The zigzag form of the displacement is incorporated via the Murakami zigzag function. Results are presented for both mechanical and thermal loading for various layups and they are validated against the derived elasticity solution. The significance of retaining various higher-order terms in the present model HSDT13, in evaluating the stresses and deflection for composite laminates is brought out clearly through parametric study. Useful results for combined hygrothermal loading are presented in tabular and graphical form. It is expected that the numerical results presented herein will serve as benchmark in future. Finally, the effect of temperature/hygroscopic dependent material properties on the hygrothermal analysis of laminated cylindrical shell strip is investigated and useful results were generated and presented in a tabular and graphical form.